Cardiac imaging : a core review - Hsu, Joe Y.; Shah, Amar; Jeudy, Jean (Core review series., 2016)
"The Core Review Series will be the first and only reference specifically designed for the new exam. This title will consist of approximately 300 questions, in a format similar to the exam with image-rich MCQs. Answers to the questions will be discussed in a concise manner along with explanations of each choice followed by relevant references. Cardiac Imaging: A Core Review will cover questions ranging from basic imaging, normal anatomy, all diseases relative to cardiac imaging, all modalities, and postoperative appearances of devices. Key Features Image-rich review text with 300 questions-includes answers and explanations. On average, each question will have 1-2 corresponding images. Bundled with an Inkling version for interactive and mobile review. High-yield tables embedded in the answers. Answers to the questions with explanations on why a particular answer choice is correct and why the other choices are incorrect"--